The Book of conviviality in exile (Kitāb al-īnās bi-'l-jalwa) : the Judaeo-Arabic translation and commentary of Saadia Gaon on the Book of Esther - Wechsler, Michael G. (Biblia Arabica, 2015)
This volume presents a critical edition of the Judaeo-Arabic translation and commentary on the book of Esther by Saadia Gaon (882-942). This edition, accompanied by an introduction and extensively annotated English translation, affords access to the first-known personalized, rationalistic Jewish commentary on this biblical book. Saadia innovatively organizes the biblical narrative-and his commentary thereon-according to seven "guidelines" that provide a practical blueprint by which Israel can live as an abased people under Gentile dominion. Saadia's prodigious acumen and sense of communal solicitude find vivid expression throughout his commentary in his carefully-defined structural and linguistic analyses, his elucidative references to a broad range of contemporary socio-religious and vocational realia, his anti-Karaite polemics, and his attention to various issues, both psychological and practical, attending Jewish-Gentile conviviality in a 10th-century Islamicate milieu.